Frequency of turner syndrome: findings from a tertiary healthcare diagnostic laboratory of India - Pande, Shailesh; Salaskar, Vidya; Pais, Anurita; Pradhan, Gauri; Patil, Smita; Parab, Chaitali; Matkar, Sunmeet (International Journal Of Community Medicine And Public Health, 2017)
Background: Turner syndrome (TS) is the most common chromosomal abnormality reported in the females. Objective of this retrospective study was to determine the frequency of turner Syndrome and its various cytogenetic types in samples suspected to be of turner syndrome, received in the Department of Cytogenetics, Metropolis Healthcare laboratory, Mumbai, Maharashtra, India. Methods: The current study was performed on 935 clinically suspected samples with Turner Syndrome within the age group of 01-16 years. Peripheral blood (2-3 ml) in Sodium heparin Vacutainers was collected from all the patients, the cultures were set & analysed by GTG–banding at 450-550 band level Results were reported as per the guidelines of the International System for Human Cytogenomic Nomenclature (ISCN) and The College of American Pathologists (CAP) and National Accreditation Board for Testing and Calibration Laboratories (NABL). Results: In our study, out of the total 935 samples referred to Metropolis Healthcare Ltd, about 348 had cytogenetically turner or Turner variant findings. Further, out of 348 cases, 69 cases were detected to have presence of single X chromosome (19.83%), mosaic pattern in 116 cases (33.33%), presence of Y chromosome in 63 cases (18.10%) polymorphic variation in 58 cases (16.67%), presence of only isochromosome Xq in 9 cases (2.59%) and 33 cases (9.48%) with other or additional abnormalities. Conclusions: The cytogenetic confirmation and pattern of chromosomal aberration is very important as early detection may help to improve the quality of life especially in patients with cytogenetically Turner variant pattern with presence of Y chromosome.